2018
DOI: 10.3390/w10010073
|View full text |Cite
|
Sign up to set email alerts
|

The Synergic Characteristics of Surface Water Pollution and Sediment Pollution with Heavy Metals in the Haihe River Basin, Northern China

Abstract: Aquatic environmental deterioration is becoming a serious problem due to rapid urbanization and economic development, particularly in developing countries. As two important components of the aquatic environment, water quality and sediment pollution are widely considered to be concerns; however, they are considered separately in most cases. The relationship between water quality and sediment pollution with heavy metals has been little addressed. In this study, the Haihe River Basin (HRB), one of the most pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The average concentration of Zn was 115.70 mg/kg, which is lower than that of Xiaobai River sediment (0.16 mg/kg), and higher than that of Yellow River (81.8 mg/kg) (Li et al 2014). The average concentration of As was 27.77 mg/kg, higher than that of Bortala (9.67 mg/kg) and Haihe Basin (7.56 mg/kg) (Kong et al 2018;Zhang et al 2016b). The average concentration of Cd was 0.23 mg/kg, lower than that of Xiaobai River (0.37 mg/kg), and similar to that of Haihe Basin (0.2 mg/kg) (Kong et al 2018;Li et al 2014).…”
Section: Spm Heavy Metal Concentrationsmentioning
confidence: 75%
“…The average concentration of Zn was 115.70 mg/kg, which is lower than that of Xiaobai River sediment (0.16 mg/kg), and higher than that of Yellow River (81.8 mg/kg) (Li et al 2014). The average concentration of As was 27.77 mg/kg, higher than that of Bortala (9.67 mg/kg) and Haihe Basin (7.56 mg/kg) (Kong et al 2018;Zhang et al 2016b). The average concentration of Cd was 0.23 mg/kg, lower than that of Xiaobai River (0.37 mg/kg), and similar to that of Haihe Basin (0.2 mg/kg) (Kong et al 2018;Li et al 2014).…”
Section: Spm Heavy Metal Concentrationsmentioning
confidence: 75%
“…The evaluation of irrigation water noted above is based on the composition of major ions, but harmful effects on human health from potentially toxic elements in water are also of great concern. Research studies have shown that in developed countries and regions, potentially toxic elements have already had a significant impact on human health 50 , 51 . There is a particular gap in the study and evaluation of potentially toxic elements in the surface waters of Central Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment factor is widely applied to quantify the abundance of metals in sediments, the levels of enrichment and to distinguish sources of metals, whether they are derived from an anthropogenic or natural source (Al Obaidy et al 2014;Kong et al 2018;Zhao et al 2017).…”
Section: Enrichment Factor (Ef)mentioning
confidence: 99%